Minimization of power loss by evolutionary programming using Thyristor Controlled Series Compensators (TCSC) / Fazleza Abdul Latiff - Abdul Latiff, Fazleza (2007)
This thesis presents an approach to minimize the power loss in distribution system. Power loss can be reduced by inserting Flexible Alternating Current Transmission Systems (FACTS) device which in the system. Thyristor Controlled Series Compensators (TCSC) is one type of FACTS device can be inserted directly in series with transmission line. TCSC is also more economical than other competing FACTS technology. TCSC provide fast speed of response and executes any switching patterns without restrictions. The main benefits of TCSC are increased energy transfer, dampening of power oscillations, dampening of sub synchronous resonances, and control of line power flow. This approach is done by using Evolutionary Programming (EP) technique. EP search for the optimal solution by evolving a population of candidate solutions, over a number of generations or iterations. The evolution of solution is carried out through mutation and competitive selection. The best generation of power loss can be obtained after running EP program. The technique was tested on the 12-Bus Radial Distribution System. Result from the study has revealed that TCSC is able to minimize loss in power distribution system.